Radicales libres y desarrollo embrionario (1999)
ABSTRACT: Until now, the study of mammalian development, as well as practical applications of information obtained from in vitro fertilization and embryo transfer, have both been hampered by changes in embryonic development frequently observed during culture. One of the causes of these changes seems to be the uncontrolled production of oxygen reactive species (ORSs). Although it is difficult to pinpoint the sources of ORSs, two factors are known to play an important role-the composition of atmospheric gas and embryo metabolism. The evidence is based on increased rates of development in the presence of either various scavengers of free radicals or reduced concentrations of oxygen in the culture medium. These results suggest that in vivo environment includes mechanisms which, in the former case, destroy or remove free radicals or, in this second, that ORSs are not produced there due to the limited availability of oxygen it we could definitively identify the sources and pathways of the ORSs, their effects could be productively controlled.